Comprehensive Analysis of the Triterpenoid Saponins Biosynthetic Pathway in Anemone flaccida by Transcriptome and Proteome Profiling - Zhan, Chuansong; Li, Xiaohua; Zhao, Zeying; Yang, Tewu; Wang, Xuekui; Luo, Biaobiao; Zhang, Qiyun; Hu, Yanru; Hu, Xuebo (Frontiers in Plant Science, 2016)
Background:Anemone flaccida Fr. Shmidt (Ranunculaceae), commonly known as ‘Di Wu’ in China, is a perennial herb with limited distribution. The rhizome of A. flaccida has long been used to treat arthritis as a tradition in China. Studies disclosed that the plant contains a rich source of triterpenoid saponins. However, little is known about triterpenoid saponins biosynthesis in A. flaccida. Results: In this study, we conducted the tandem transcriptome and proteome profiling of a non-model medicinal plant, A. flaccida. Using Illumina HiSeq 2000 sequencing and iTRAQ technique, a total of 46,962 high-quality unigenes were obtained with an average sequence length of 1,310 bp, along with 1473 unique proteins from A. flaccida. Among the A. flaccida transcripts, 36,617 (77.97%) showed significant similarity (E-value < 1e-5) to the known proteins in the public database. Of the total 46,962 unigenes, 36,617 open reading frame (ORFs) were predicted. By the fragments per kilobases per million reads (FPKM) statistics, 14,004 isoforms/unigenes were found to be upregulated, and 14,090 isoforms/unigenes were down-regulated in the rhizomes as compared to those in the leaves. Based on the bioinformatics analysis, all possible enzymes involved in the triterpenoid saponins biosynthetic pathway of A. flaccida were identified, including cytosolic mevalonate pathway (MVA) and the plastidial methylerythritol pathway (MEP). Additionally, a total of 126 putative cytochrome P450 (CYP450) and 32 putative UDP glycosyltransferases were selected as the candidates of triterpenoid saponins modifiers. Among them, four of them were annotated as the gene of CYP716A subfamily, the key enzyme in the oleanane-type triterpenoid saponins biosynthetic pathway. Furthermore, based on RNA-Seq and proteome analysis, as well as quantitative RT-PCR verification, the expression level of gene and protein committed to triterpenoids biosynthesis in the leaf versus the rhizome was compared. Conclusion: A combination of the de novo transcriptome and proteome profiling based on the Illumina HiSeq 2000 sequencing platform and iTRAQ technique was shown to be a powerful method for the discovery of candidate genes, which encoded enzymes that were responsible for the biosynthesis of novel secondary metabolites in a non-model plant. The transcriptome data of our study provides a very important resource for the understanding of the triterpenoid saponins biosynthesis of A. flaccida.